2019
DOI: 10.1029/2018jc014766
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variability of Near‐Surface Oxygen in the Strait of Georgia

Abstract: Dissolved oxygen (O2) concentrations in waters of the ocean surface mixed layer are generally close to thermodynamic equilibrium with atmospheric concentrations. However, near‐surface O2 levels are also affected by other processes, including primary productivity, and thus measurements of near‐surface O2 can in theory be used to estimate productivity. Here we discuss variations in near‐surface O2 concentrations in the Strait of Georgia by examining a variety of data sets, focusing primarily on ferry‐based measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The dataset is comprised of measurements acquired with autonomous sensors on board the ferry including salinity, above-water solar radiation, in vivo Chl-a fluorescence, and water samples from which Chl-a was extracted using HPLC methods. The approximate depth of intake for the ferry instruments was 2 m (Halverson and Pawlowicz, 2013;Wang et al, 2019). Salinity was used to separate plume dominant plume and oceanic dominate waters, and, as a proxy to determine the photosynthetic active radiation (PAR) attenuation coefficient at 2 m depth (k z ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dataset is comprised of measurements acquired with autonomous sensors on board the ferry including salinity, above-water solar radiation, in vivo Chl-a fluorescence, and water samples from which Chl-a was extracted using HPLC methods. The approximate depth of intake for the ferry instruments was 2 m (Halverson and Pawlowicz, 2013;Wang et al, 2019). Salinity was used to separate plume dominant plume and oceanic dominate waters, and, as a proxy to determine the photosynthetic active radiation (PAR) attenuation coefficient at 2 m depth (k z ).…”
Section: Methodsmentioning
confidence: 99%
“…To address these limitations, in vivo fluorometers are used to continuously measure the fluorescence of the chlorophyll-a pigment, following the principles introduced by Lorenzen (1966). In vivo fluorometers are routinely installed on floats, gliders, profiling systems (Davis et al, 2008;Thomalla et al, 2018), moored platforms (Falkowski and Kolber, 1995), animals (Biermann et al, 2015;Xing et al, 2012), and ships of opportunity (Holley et al, 2007;Halverson and Pawlowicz, 2013;Anderson et al, 2017;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent observational study (Leighton et al, 2018), however, concluded that bubble‐induced supersaturation is more important than previously thought, implying that existing CO 2 calculations neglecting bubble‐induced supersaturation may overestimate (underestimate) efflux (influx). On the other hand, the importance of bubble‐induced supersaturation for less soluble gases such as O 2 (e.g., Bushinsky et al, 2016; Vagle et al, 2010; Wang et al, 2019), inert gases (Stanley et al, 2009), and their ratios (e.g., Hamme & Emerson, 2006) has already been recognized. It was also established in those studies that accurate quantification of the total air‐sea gas flux requires the separation of the total gas flux into three components, viz., the gas flux through the ocean surface, that through bubbles that completely dissolved, and that through bubbles that eventually burst at the ocean surface (partially dissolved).…”
Section: Introductionmentioning
confidence: 99%